Characteristics of subacute stroke patients who achieve earlier independence in real-life walking performance during hospitalization - Kenji Kawakami; Shigeo Tanabe; Daiki Kinoshita; Ryo Kitabatake; Hiroo Koshisaki; Kenta Fujimura; Yoshikiyo Kanada; Hiroaki Sakurai (Journal of Rehabilitation Medicine)
Objective: To identify factors associated with earlier independence in “real-life walking” during hospitalization in subacute stroke patients.